Spontaneous Periodic Deformations in Nonchiral Planar-Aligned Bimesogens with a Nematic-Nematic Transition and a Negative Elastic Constant - VIJ, JAGDISH KUMAR; PANARIN, YURI PETROVICH (My University, 2010)
Hydrocarbon linked mesogenic dimers are found to exhibit an additional nematic phase below the conventional uniaxial nematic phase as confirmed by x-ray diffraction. The phase produces unusual periodic stripe domains in planar cells. The stripes are found to be parallel to the rubbing direction (in rubbed cells) with a well-defined period equal to double the cell gap. The stripes appear without external electromagnetic field, temperature or thickness gradients, rubbing or hybrid alignment treatments. Simple modeling proposes a negative sign for at least one of the two elastic constants: splay and twist, as a necessary condition for the observed pattern.
PUBLISHED
Keywords: Physics